Occurrence and significance of phytanyl arenes across the Permian-Triassic boundary interval. (February 2017) - Grotheer, H.; Le Métayer, P.; Piggott, M.J.; Lindeboom, E.J.; Holman, A.I.; Twitchett, R.J.; Grice, K.
Highlights: Phytanyl benzene and phytanyl toluene occur in mudstones from several key PTB sections. Occurrence through different PTB sections is related to occurrence of C33 n -alkyl cyclohexane. Absent from palaeoequatorial, Global Stratotype Section and Point (GSSP), Meishan-1 (South China). Lack in carbonate lithology possibly points to source being temperature and climate controlled. Abstract: Phytanyl benzene and phytanyl toluene occur in mudstones from several key Permian-Triassic Boundary (PTB) sections from mid-northern palaeolatitudes (Spitsbergen and Eastern Greenland), as well as mid-southern palaeolatitudes (Western Australia). The occurrence of these compounds through the different PTB sections is related to the occurrence of the previously identified C33 n -alkyl cyclohexane, suggesting their parent organism shared a similar unique ecological niche and was associated with the extinction horizon. Further, the lack of these compounds in the carbonate-dominated palaeoequatorial, Global Stratotype Section and Point (GSSP), Meishan-1 (South China) section possibly points to their source being temperature and climate controlled.